Música en el sistema educativo japonés: de la moral imperial a la sociedad 5.0 - Gazzano, Alan (El Colegio de México, 2022)
Since 2020, the incorporation of “programming education” into all elementary school subjects in Japan has raised questions about its implications in areas such as music education. This study aims to contextualize that reform in the history of music education in Japan, as well as to examine its key concepts on the basis of Japanese curricular guidelines and reports on its implementation in music. Findings suggest that, while the moralizing intent of the music curriculum remains, incorporating programming may have favored exploratory learning with software, alongside the adoption of computer science jargon in music activities. However, it may also outline new roles for music as a subject in the school curriculum. In that context, music would serve human resource development needs  for the realization of Society 5.0, one of Japan’s latest socioeconomic goals.